Selective Isotopic Unlabeling of Proteins Using Metabolic Precursors: Application to NMR Assignment of Intrinsically Disordered Proteins - RASIA, Rodolfo Maximiliano (2012)
Selective isotopic unlabeling of proteins can provide important residue-type information as well as reduce congestion of NMR spectra. However, metabolic scrambling often complicates the final isotope-labeling pattern. Here, an array of metabolic precursors is used to perform robust, residue-specific unlabeling of proteins. The resulting isotopic-labeling patterns are predictable and nicely complement NMR experiments that differentiate residue types. This approach has widespread applications, but it is particularly relevant for proteins that lack sequence complexity or a defined tertiary structure.